Inovasi Administrasi Perpajakan Dalam Optimalisasi Penerimaan Pajak Daerah (Studi Pemasangan Tapping Box Pada Pajak Hotel, Restoran Dan Hiburan Di Kota Kendari) - Firdaus, Firdaus (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2020)
This study aims to explain tax administration innovations in managing the productive taxation human resources. The results of this study indicate that the Government of Kendari City has formed a collaboration through a Memorandum of Understanding with the Corruption Eradication Commission (KPK) in the Field of Coordination, Supervision and Prevention (Korsubgah) and Bank Sultra. One of the agreements that was built was the cooperation in installing tax recording devices (tapping boxes) in hotel, restaurant and entertainment businesses. The legality of the application of this tax transaction tool is regulated in the Kendari Mayor Regulation Number 24 of 2019 concerning Online System Payments and Collections of Local Taxes and Levies through a Tax Recording Tool. The application of tapping boxes has had a very positive impact on the amount of regional revenue compared to before the installation of these tools. This can be seen in the hotel tax revenue in 2018 amounting to Rp. 8.76 billion increased to Rp. 12.7 billion in 2019. Restaurant tax revenue in 2018 was Rp. 11.2 billion to Rp. 16 billion increased in 2019. Then entertainment tax revenue in 2018 amounted to Rp. 7.2 billion increased to Rp. 8.5 billion in 2019. The number of tapping box installations in Kendari City has also increased from 76 units to 464 units by October 2020. Therefore, it is necessary to increase the effectiveness of cooperation from various parties in organizing a tapping box application program to optimize tax revenue for hotels, restaurants and entertainment is an innovation in tax administration to build productive and digital-based tax human resources. Therefore, it is necessary to increase cooperation from various parties in implementing a tapping box application program to optimize hotel, restaurant and entertainment tax revenue to create effectiveness and efficiency in an innovation of tax administration to build productive and digital-based tax human resources.